Analisis Penanganan Bagasi Hilang Oleh Petugas Lost And Found PT Kokapura Avia Pada Maskapai Lion Air Di Bandar Udara Internasional Yogyakarta - Nada Akram Zaiyan Subroto; Kartika Fajar Nieamah (Student Research Journal, 2023)
PT Kokapura Avia has many work units. One of the PT Kokapura Avia is a lost and found unit. Lost and found is a place for passengers to report if their baggage is lost or damaged (SOP/ aas-aqp - 001/2019). The principal task of lost and found is to check the baggage number on the passenger with the baggage label on it, caring for any excess and shortages or damage to luggage experienced by a passenger. The reason for the lack of passenger luggage is that an employee's labeling or misloading of luggage onto another flight. The deviation of the baggage services usually takes place when passengers arrive at the terminal. As for the research, it is aimed at locating the missing baggage tracing and storage system and the application of cooperation between Lion Air and International Airport Yogyakarta in lost baggage tracing of lost and found PT Kokapoura Avia. The study uses qualitative research methods. By using data collection techniques of observation, interview and documentation. Interviews use semi-structured techniques and data analysis using three techniques which are data reduction, data display and deduction drawing. Based on the result show the preparation of the lost and found provides a pear (an arity report source) used to screened the baggage claim by passengers. They include passenger identification and claim tag statements that are already matched with data found in the system of the lost and found unit. There are two courses of tracing that are tracing by CCTV and tracing by E-mail. Yogyakarta's international airport operations provide facilities and CCTV services in cooperation while lion air airlines provide a system that is used by lost and found and is responsible for providing compensation to passengers.